PROCEDURE FOR CRIMINAL PROCEEDINGS NOT TO PAY SEVERANCE PAY IS AN ULTIMUM REMEDIUM - Fauzan; Suci Ramadani (Yayasan Multidimensi Kreatif, 2026)
Severance pay is a workers' right arising from termination of employment and must be fulfilled by employers in accordance with the provisions of labor law. In practice, there are still entrepreneurs who do not pay severance pay even though the obligation has been determined through agreements, court decisions, or the provisions of laws and regulations. This study aims to analyze the procedures for the implementation of criminal proceedings against employers who do not fulfill the obligation to pay severance pay and examine the position of criminal law as a last resort or ultimum remedium in resolving labor disputes. The research uses a combination of normative and empirical methods. The normative approach is carried out through the study of labor regulations, criminal law, legal doctrine, and court decisions. The empirical approach is carried out by examining the implementation of law enforcement in cases of non-payment of severance pay. The results of the study show that criminal proceedings can be applied if the employer deliberately does not carry out the obligation to pay severance pay that already has a clear legal basis. The process begins with dispute resolution through bipartite negotiations, mediation or conciliation, and mechanisms at the Industrial Relations Court. If the obligation is still not carried out and the act meets the elements of an employment crime, the worker can make a report to the labor supervisor or law enforcement officials. However, the application of criminal law should be placed as the ultimum remedium after administrative, civil, and industrial relations settlement efforts have yielded no results. The application of these principles is necessary to maintain a balance between the protection of workers' rights, legal certainty, and the proportionality of law enforcement.